PENDAMPINGAN PENERAPAN DIGITAL MARKETING BERBASIS WEBSITE UNTUK PETERNAK AYAM DI KOTA PAREPARE - Wahrini, Retyana; Hasbi, Hasbi (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
Highly developed technology is utilized for various purposes, including by MSMEs. Most people feel that technology has an impact on independence, especially internet use. Utilization of the internet as a means of information technology to carry out business activities for MSMEs. This Community Service Activity aims to provide education through counseling regarding the use of website-based digital marketing as a promotional and marketing medium in the livestock sector in the city of Parepare, South Sulawesi. The method used in this service uses the ABCD method, which provides assistance in implementing website-based digital marketing for chicken farmers in the city of Parepare. The result of this Community Service activity is that mentoring has had a positive impact on chicken farmers in Parepare City in the form of increasing sales, increasing brand awareness, strengthening skills, and improving product quality. In this training, the role of companions is very important in providing support, guidance and motivation for the community. With this community service, people in Parepare City can increase their knowledge about the use of website-based digital marketing as an effective means of promoting and marketing livestock products. The results of the participant evaluation after attending training on the use of website-based marketing media, 100% of participants stated that they strongly agreed with using website-based marketing media for promotional media for chicken farming products. Of the 20 chicken farmer participants who took part in the training, most have understand how to do website-based online marketing.